Chronic use of statins and risk of post-ERCP acute pancreatitis (STARK): Study protocol for an international multicenter prospective cohort study. Issue 12 (December 2018) - Korpela, Taija; Cárdenas-Jaén, Karina; Archibugi, Livia; Poropat, Goran; Maisonneuve, Patrick; Arcidiacono, Paolo Giorgio; De Pretis, Nicolò; Löhr, Matthias; Capurso, Gabriele; de-Madaria, Enrique
Abstract: Background: Acute pancreatitis (AP) is the most common complication after endoscopic retrograde cholangiopancreatography (ERCP). Statins have been traditionally associated to an increased risk of AP, however, recent evidence suggests that statins may have a protective role against this disease. Aims: Our primary aim is to investigate whether the use of statins has a protective effect against post-ERCP pancreatitis (PEP). Secondary outcomes are: to evaluate the effect of other drugs on the incidence of PEP; to ascertain the relationship between the use of statins and the severity of PEP; and to evaluate the effect of other risk and protective factors on the incidence of PEP. Methods: STARK is an international multicenter prospective cohort study. Centers from Spain, Italy, Croatia, Finland and Sweden joined this study. The total sample size will include about 1016 patients, which was based on assuming a 5% incidence of PEP among non-statin (NSt) users, a 1–3 ratio of statin (St) and NSt consumers respectively, a 70% decrease in PEP among St consumers, an alpha-error of 0.05 and beta-error of 0.20. All patients aged ≥18 years scheduled for ERCP will be offered to enter the study. Discussion: STARK study will ascertain whether statins, a safe, widely used and inexpensive drug, can modify the incidence of PEP.